Psychiatric co-morbidity among patients with primary headache - Syed, Sifat E; Mullick, MSI; Hannan, MA (Bangladesh Journal of Psychiatry, 2020)
Headache is the commonest complaint in neurology outpatient departments (OPD) and the co- existence of psychiatric disorders with headache is an established fact. This study was aimed to estimate the proportion of adult headache patients suffering from psychiatric co-morbidity and to see the possible association between headache pattern and psychiatric disorders.This cross sectional study was done among 51 sample of neurology OPD of BSMMU. International Classification of Headache Disorders (ICHD-3) was used to determine the types of headache and Mini International Neuropsychiatric Interview (MINI) was used to diagnose psychiatric disorder. Purposive sampling technique was used and data was collected using face-to-face interview from January, 2015 to June, 2015. New and old cases of primary headache of both sexes who were 15-65 years old were taken as samples. The results found that tension type headache was the commonest type of headache and total 62.7% of headache patients suffered from psychiatric disorder. Among them, 39.2% had depressive disorder and 17.6% had anxiety disorders. Logistic regression revealed that higher duration and frequency of headache was a predictor of having psychiatric comorbidity (OR= 1.7). This small study shows the need of larger research in this issue and also points out the importance of psychiatric intervention for headache patients. Bang J Psychiatry December 2016; 30(2): 32-35